2014
DOI: 10.1055/s-0034-1366247
|View full text |Cite
|
Sign up to set email alerts
|

Split-Bolus Single-Phase Cardiac Multidetector Computed Tomography for Reliable Detection of Left Atrial Thrombus: Comparison to Transesophageal Echocardiography

Abstract: Ziel: Evaluierung eines neuen Kardio-MDCT-Protokoll mit Doppel-Bolus-Injektion zur Verbesserung der Detektion von LA-oder LAA-Thromben und Reduzierung falsch positiver Befunde im Vergleich zu den Ergebnissen der transösophagealen Echokardiografie (TEE). Purpose: Evaluation of a new cardiac MDCT protocol using a split-bolus contrast injection protocol and single MDCT scan for reliable diagnosis of LA/LAA thrombi in comparison to TEE, optimizing radiation exposure and use of contrast agent. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a study by Shapiro et al, the sensitivity changed from 80 % to 70 %, the specificity from 73 % to 82 %, the PPV from 54 % to 47 % and the NPV from 90 % to 92 % [19]. However, other studies reported an additional diagnostic benefit from the use of relative HU ratios for the detection of thrombi [20,21]. Possible reasons for the difference in the influence of relative HU ratios on the diagnostic accuracy of MD-CT are the heart rate and rhythm at the time of MD-CT (sinus rhythm vs. atrial fibrillation), the type of scan triggering (fixed time interval vs. bolus tracking), the type of contrast media injection (e. g. monophasic, biphasic), use of ECG gating [17,22], and the number of detector rows [23].…”
mentioning
confidence: 97%
“…In a study by Shapiro et al, the sensitivity changed from 80 % to 70 %, the specificity from 73 % to 82 %, the PPV from 54 % to 47 % and the NPV from 90 % to 92 % [19]. However, other studies reported an additional diagnostic benefit from the use of relative HU ratios for the detection of thrombi [20,21]. Possible reasons for the difference in the influence of relative HU ratios on the diagnostic accuracy of MD-CT are the heart rate and rhythm at the time of MD-CT (sinus rhythm vs. atrial fibrillation), the type of scan triggering (fixed time interval vs. bolus tracking), the type of contrast media injection (e. g. monophasic, biphasic), use of ECG gating [17,22], and the number of detector rows [23].…”
mentioning
confidence: 97%
“…In all studies, almost 100% values of sensitivity, specificity, positive and negative predictive values for imaging of thrombotic masses were obtained. However, the impact of this contrast enhancement technique on the imaging quality of right chambers has not been assessed [27].…”
Section: Intermediate Results Of Non-invasive Cardiac Mapping: Volumetric Epicardial Atrial Models (A C E -Left Atrium B D F -Right Atriumentioning
confidence: 99%